Implementasi Pengajaran Rasul Paulus Tentang Kasih Berdasarkan 1 Korintus 13:1-13 Bagi Siswa SMP Joseph Khatulistiwa Sintang Kalimantan Barat - Harmanus, Harmanus; Suparti, Hana; Uriptinigsih, Ana Lestari (Sekolah Tinggi Teologi Kadesi Yogyakarta, 2023)
The aim of the study was to find out the level of implementation of the apostle Paul's teaching about love based on 1 Corinthians 13:1-13 for students of SMP Joseph Khatulistiwa. The method used is quantitative. Collecting data through a Likert scale and processing it through several tests using SPSS 25. The tests used are validation and reliability tests of instruments as well as normality tests, homogeneity tests, and hypothesis testing. The results show that the level of implementation of the apostle Paul's teaching about love based on 1 Corinthians 13:1-13 for students of SMP Joseph Khatulistiwa Sintang, West Kalimantan, is in the moderate category and the results are the same as the hypothesis proposed.